The Transformation of Students’ Academic Literacy in the Era of Generative Artificial Intelligence: Opportunities, Challenges, and Ethical Implications - Didy Fantofik (Journal of Pedagogi, 2026)
The rapid diffusion of generative artificial intelligence (GenAI) tools such as ChatGPT, Gemini, and Claude has reshaped how university students read, write, think, and produce academic knowledge. This article synthesizes scholarship published between 2023 and 2026 to examine the transformation of students' academic literacy, understood as skills required to locate, evaluate, synthesize, and ethically communicate knowledge, in the GenAI era. Employing a narrative-systematic literature review of thirty peer-reviewed sources indexed in Scopus, Web of Science, and IEEE Xplore, the study maps three interlocking dimensions of transformation: opportunities such as personalized feedback and scaffolded drafting, challenges including overreliance and erosion of critical thinking, and ethical implications concerning authorship ambiguity and academic integrity. Findings indicate that GenAI functions simultaneously as a cognitive amplifier and a literacy risk, contingent on students' metacognitive regulation and institutional guardrails. The novelty of this review lies in proposing an integrative Academic Literacy and Generative AI framework that repositions academic literacy not as a static skill threatened by artificial intelligence, but as a dynamic, co-regulated competency requiring explicit prompt literacy, verification literacy, and ethical literacy. The article concludes that sustainable integration of generative AI in higher education depends on redesigning assessment practices, embedding artificial intelligence literacy curricula, and establishing transparent disclosure norms rather than prohibition-based policies.